2019
DOI: 10.31384/jisrmsse/2019.17.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Financial Constraints on the Performance of SMEs - A Study of Sindh Province

Abstract: SMEs have been efficiently used as the vehicles for promoting innovation, productivity, and the competitiveness of a country's national economy. Across the globe, SMEs have been playing a distinctive role in achieving the socioeconomic objectives such as employment generation, poverty reduction, equalizing the distribution of national wealth, fostering innovation, and nurturing institutional competitiveness. The main objective of this study is to empirically examine the extent to which financial constraints ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Third, financial constraints are a first-order construct of which questions were adapted from Shaikh & Khoso (2019). There are seven questions focusing on internal financing obstructions, external financing, stringent collaterals, inadequate facilities, financial institutions' constraints, cost of borrowing, and procedure of obtaining loans.…”
Section: Construct Measurementmentioning
confidence: 99%
“…Third, financial constraints are a first-order construct of which questions were adapted from Shaikh & Khoso (2019). There are seven questions focusing on internal financing obstructions, external financing, stringent collaterals, inadequate facilities, financial institutions' constraints, cost of borrowing, and procedure of obtaining loans.…”
Section: Construct Measurementmentioning
confidence: 99%
“…Perceived by the Small and Medium Enterprises (SMEs) in the Apparel Export Sector of Pakistan (Khan, 2017). Some remote analyst dissects the effect of mechanical advancement on SME's productivity in Nigeria (Adepoju, Olomu, and Akinwale, 2017 (Shaikh & Khoso, 2019a). After the analysis of these impacts, our study is to find the Effect of Gross Domestic Product (GDP) on performance of SMEs Sector in Pakistan.…”
Section: Journal Of Entrepreneurship Management and Innovationmentioning
confidence: 99%
“…In an examination directed by Beck and Demirguc-Kunt ( 2006 (1999)(2000) led in 80 nations with an example size of 10,000 firms indicated that the organizations which announced access to financing as an extreme limitation has encountered a moderate yield development (Beck, Demirguc-Kunt, and Levine, 2005). A lot of the observational writing on the investigation of financing requirements has inferred that SMEs face financing hindrances as a result of organization issue and lopsided data among banks and the little firms (Blundell, Dearden, and Meghir, 1996;Bond, Harhoff, and Van Reenen, 1999;Shaikh & Khoso, 2019a)…”
Section: Journal Of Entrepreneurship Management and Innovationmentioning
confidence: 99%
“…SMEs can be used as a tool in the promotion of productivity, competitiveness, and innovation in the national economy of the country. The distinctive role has been enacting by the SMEs to achieve socio-economic objectives like reducing poverty, producing employment opportunities, nurturing innovation, and fostering competitiveness among institutions (Shaikh & Khoso, 2019). In both developing and developed economies, the SMEs potential in nurturing economic growth is extensively appreciated and cited by policymakers and academic scholars as well.…”
Section: Literature Reviewmentioning
confidence: 99%